Procedural Generation of a 3D Terrain Model Based on a Predefined Road Mesh - Bengtsson Burhöi, Fredrik; Gelotte, Bjarne; Graul Sagdahl, Jonas; Berger, Kim; Kvarnström, Sebastian; Andersson, Matilda (My University, 2017)
This thesis studies procedural generation as a method for generating a realistic terrain model, that will be used as a part of a virtual environment for testing the cameras of autonomous vehicles. The project was done in collaboration with Volvo Cars, and resulted in software that was able to generate a terrain model with only a mesh representing a road as input according to the customer’s requirements. Specifically, the purpose of the thesis was to develop software that was able to fit the generated terrain model to a road, place ditches alongside it, make the terrain model surrounding the road resemble a hilly landscape, and decide what type of terrain each mesh should represent. The functionality to base the look of the terrain model on real world height data was also implemented. Radial basis function interpolation was used to fit the terrain model to the road, and Perlin noise, Simplex noise, and Worley noise were used to modify the topography of the terrain model. The ditches were created by projecting parts of the terrain model to fit a cylindrical shape, and the type of terrain a mesh should represent is based on the distance between the mesh and the road. The end result shows that it is possible to use procedural generation to create realistic terrain models, and the generated models can be used as a part of virtual testing environments. However, the software is more a proof of concept than a finished solution, and there are several areas in need of improvement such as implementing support for more terrain types, being able to use more than one noise map, and improving how the ditches interact with noise. For future research Volvo Cars has expressed interest in expanding the scope of the product to allow for generation of suburban areas, as well as mountains and include support for tunnels.
Keywords: Data- och informationsvetenskap; Computer and Information Science